Comparison of cadmium manganese telluride crystals grown by traveling heater method and vertical Bridgman method. Issue 11 (17th August 2015) - Lai, Jianming; Zhang, Jijun; Wang, Linjun; Min, Jiahua; Wu, Wenqi; Shen, Min; Liang, Wei
Abstract : The CdMnTe crystals were grown by the travelling heater method and the vertical bridgman method, respectively. The crystal properties, including the Mn axial distribution, impurity concentrations, resistivity, Hall effects and energy response spectra, were characterized and compared. The results demonstrate that CdMnTe crystal grown by travelling heater method have better crystal quality and detector properties compared to that by vertical bridgman method. Abstract : In this paper, the CdMnTe crystals were grown by the Travelling Heater Method (THM) and the Vertical Bridgman (VB) method, respectively. The crystal properties, including the Mn axial distribution, impurity concentrations, resistivity, Hall effects and energy response spectra, were characterized and compared. The results shown that the CdMnTe crystal grown by the THM had more uniform Mn distribution and lower impurity concentrations compared to the crystal grown by VB method. The resistivity of CdMnTe grown by THM was (1.5 ∼ 8) × 10 10 Ω.cm, while the resistivity of CdMnTe grown by VB was 10 7 ∼10 8 Ω.cm. The In dopant distributed uniformly throughout the crystal ingot grown by THM with the doping concentration of 0.6–0.7 ppm, while the In dopant concentration throughout the crystal grown by VB method is in the range of 1.31–2.4 ppm. Hall measurements revealed that the conductivity of the THM grown crystal was weak n‐type conductivity and the VB grown crystal was p‐type conductivity. A planar CdMnTe detector from the THM grown crystal showed a resolution of 8% of the 241 Am radiation at 59.5 keV peak, however, no energy response was revealed with the CdMnTe detector by the VB method. The results demonstrate that CdMnTe crystal grown by THM have better crystal quality and detector properties compared to that by VB method.